Factors Influencing Gen-Y Green Purchasing Behavior In Malaysia - Chong , Tun Cheng (2011)
This research has been designed to examine the factors that are capable of influencing the consumers\' Green Purchasing Behavior in the context of the Malaysians\' Generation Y.